The experience of PRODEMA in Brazilian postgraduate education: science for sustainability at UFC - Rabelo, Laudemira Silva; Rabelo, Melca Silva; Freire, George Sá; Oliveira, Vládia Vidal; Lima, Patrícia Pinheiro (Revista Brasileira de Pós-Graduação, 2014)
Sustainability is inserted in a context in which it must be extricated from a disciplinary vision and included in the construction of complex and interdisciplinary knowledge. Rio+20 raised the urgency of moving to an inclusive economic system called Green Economy. This transformation will require new professionals and scientists that can better overcome barriers to real change. Thus, this paper aims to present the contributions of the Postgraduate Programme on Development and the Environment at the Federal University of Ceará (UFC) in the construction of interdisciplinary knowledge in the face of issues related to Sustainable Development arising in the context of graduate education and professional training.